Ascorbic Acid as an Efficient Organocatalyst for the Synthesis of 2‐Substituted‐2, 3‐dihydroquinazolin‐4(1H)‐one and 2‐Substituted Quinazolin‐4(3H)‐one in Water. Issue 1 (2nd January 2020) - Chandra Pariyar, Gyan; Mitra, Bijeta; Mukherjee, Suvodip; Ghosh, Pranab
Abstract: An environmentally benign, robust and straightforward protocol has been developed for the synthesis of a diverse array of 2, 3‐dihydroquinazolin‐4(1 H )‐ones using 2‐aminobenzamide and various aldehydes or ketones. Water, a green solvent was adopted in this methodology replacing hazardous reaction mediums. Further, ascorbic acid, an organocatalyst has been accepted to meet the role of catalyst, thus bypassing the use of noxious metals or hazardous materials, which is another asset of this protocol. The activity of this novel methodology has been further being broadened using an oxidant oxone to synthesize 2‐substituted quinazolin‐4(3 H )‐one from aldehyde. Abstract : A convenient, greener and metal‐free method has been developed to design a vast range of highly functionalized 2, 3‐dihydroquinazolin‐4(1 H )‐ones derivatives and was further extended for synthesis of 2‐substituted quinazolin‐4(3 H )‐one. These methodologies involve synthesis from inexpensive and easily available aldehydes and ketones using L‐ascorbic acid, an environment friendly organocatalyst, using the most benign water as solvent.